Limits to tDCS effects in language: Failures to modulate word production in healthy participants with frontal or temporal tDCS. (January 2017) - Westwood, Samuel J.; Olson, Andrew; Miall, R. Chris; Nappo, Raffaele; Romani, Cristina
Abstract: Transcranial direct current stimulation (tDCS) is a method of non-invasive brain stimulation widely used to modulate cognitive functions. Recent studies, however, suggests that effects are unreliable, small and often non-significant at least when stimulation is applied in a single session to healthy individuals. We examined the effects of frontal and temporal lobe anodal tDCS on naming and reading tasks and considered possible interactions with linguistic activation and selection mechanisms as well as possible interactions with item difficulty and participant individual variability. Across four separate experiments ( N, Exp 1A = 18 ; 1B = 20 ; 1C = 18 ; 2 = 17 ), we failed to find any difference between real and sham stimulation. Moreover, we found no evidence of significant effects limited to particular conditions (i.e., those requiring suppression of semantic interference), to a subset of participants or to longer RTs. Our findings sound a cautionary note on using tDCS as a means to modulate cognitive performance. Consistent effects of tDCS may be difficult to demonstrate in healthy participants in reading and naming tasks, and be limited to cases of pathological neurophysiology and/or to the use of learning paradigms.